Convective Updraft and Downdraft Characteristics of Continental Mesoscale Convective Systems in the Model Gray Zone. Issue 16 (20th August 2022) - Wang, Dié; Prein, Andreas F.; Giangrande, Scott E.; Ramos‐Valle, Alexandra; Ge, Ming; Jensen, Michael P.
Abstract: The "gray zone" of convective modeling is defined as the range of horizontal grid spacings (Δ x ) at which turbulent transport processes are only partially resolved by the dynamics of the numerical model. This zone typically covers Δ x from a few kilometers to several hundred meters, wherein the realistic representation of convective cloud processes can be challenging. This study characterizes the convective draft behaviors at multiple Δ x across the gray zone and determines the appropriate Δ x that can reliably capture these salient convective properties. We perform an ensemble of idealized simulations of mesoscale convective systems (MCS) using the Weather Research and Forecasting model at various Δ x from 4 km to 250 m over the central U.S. An evaluation of key MCS kinematic properties is constrained using unique, long‐term vertical velocity estimates obtained by radar wind profilers deployed by the Department of Energy Atmospheric Radiation Measurement user facility. MCS simulations for all Δ x tested overestimate (underestimate) the probabilities of convective updrafts (downdrafts) compared to the observations. In terms of the convective draft intensity, finer‐Δ x models overestimate the updraft intensity, while the opposite is found for downdrafts. Moving from Δ x  = 4 km to 250 m, downdrafts become stronger and more frequent especially at middle and upper levels, attributed to additional drag from an increasing graupel frequency and compensation of enhanced updraft velocity. Simulated draft characteristics, including core size, intensity, and probability of occurrence, exhibit pronounced changes at Δ x greater than 500 m, but suggest less sensitivity when Δ x is reduced below 500 m. Key Points: A unique vertical velocity data set from the Atmospheric Radiation Measurement is used for the evaluation of the simulated mesoscale convective systems in the model gray zone Finer grid spacing models simulate too large and too frequent convective updrafts Coarser grid spacing models simulate too weak and too few convective downdrafts